Anti-microbial Efficacy of Calcium-hydroxide, 0.02% Chlorhexidine, 1% Metronidazole and Chitosan as Intracanal Medicament – a Double-Blind Invitro Study - Khahro, Muhammad Muslim (International Journal of Pathology, 2022)
Introduction: Enterococcus faecalis (E.faecalis) and Candida albicans (C.albicans) are mostly found microbes in root canal failure cases. Calcium-hydroxide is most commonly used as intra-canal medicament to control infections. Recent studies show emerging resistance of Enterococcus faecalis and Candida albicans against Calcium-hydroxide, 0.02% chlorhexidine gel, 1% metronidazole gel and a bio polymer chitosan are being used as medicament for different oral infections like gingivitis, ulcers and in intra-canal irrigations. Their role as intra-canal medicament is not established. In this study, we have determined the anti-microbial efficacy of Calcium-hydroxide, chlorhexidine, metronidazole and chitosan against Enterococcus-faecalis and candida-albicans by agar diffusion test, thereby confirming their role as intra-canal medicament. Objective: In this study, we wanted to determine antimicrobial activity of 0.02% chlorhexidine gel, 1% metronidazole gel and a bio polymer chitosan and their role as intracanal medicament against E.faecalis and C.albicans using Agar diffusion method. Materials and Methods: Enterococcus faecalis and Candida albicans isolated on culture were subjected to agar diffusion on Muellar-Hinton Agar (MHA) against 1% metronidazole gel, calcium-hydroxide, chitosan and 0.02 % chlorhexidine gel. Zones of inhibition were measured after 24 hours of incubation, presence of which was interpreted as their activity against the organisms. Data was analyzed using SPSS. Results: 0.02 % chlorhexidine gel had a zone of inhibition of 10 mm and 12 mm against E.faecalis and C.albicans, suggesting that it can be used as intracanal medicament, whereas 1% metronidazole and calcium hydroxide showed minimal antimicrobial efficacy with 1 mm zone of inhibition for both isolates. Chitosan showed no zone of inhibition. Conclusion: Our study shows 0.02 % chlorohexidine gel has higher antimicrobial efficacy against E.faecalis and Candida albicans than 1% metronidazole gel, calcium hydroxide and chitosan, suggesting its use as intracanal medicament. However further studies with larger sample size; clinical samples and molecular intervention are needed to establish their role as a definite intracanal medicament.